1996
DOI: 10.1002/jlb.60.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant monocyte chemotactic protein and other c-c chemokines bind and induce directional migration of dendritic cells in vitro

Abstract: Because dendritic cells (DC) are the most potent antigen-presenting cells involved in many pathophysiological responses, we investigated the effect of chemokines on the migration of these cells in an effort to determine whether chemokines may contribute to the initiation of immune responses. CD34+ progenitor cells isolated from umbilical cord blood were grown in suspension cultures with cytokines and expanded 50- to 100-fold. A variable proportion of the cells expressed markers consistent with DC. The proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
2
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(224 citation statements)
references
References 26 publications
9
210
2
3
Order By: Relevance
“…Responses to chemokines are mediated by chemokine receptors. DC express a variety of chemokine receptors [11,12]. The migratory activity of LC/DC toward chemokines has been investigated by using a chemotaxis microchamber [61,62] or a modified Boyden chamber [63].…”
Section: In Vitro Assay For Lc Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Responses to chemokines are mediated by chemokine receptors. DC express a variety of chemokine receptors [11,12]. The migratory activity of LC/DC toward chemokines has been investigated by using a chemotaxis microchamber [61,62] or a modified Boyden chamber [63].…”
Section: In Vitro Assay For Lc Migrationmentioning
confidence: 99%
“…In vitro migration studies using a chemotaxis microchamber or a modified Boyden chamber have demonstrated that a variety of chemokines induce directional migration of DC/LC [11,12]. These chemokines include the CC chemokines, such as macrophage inflammatory protein (MIP)-1␣, MIP-1␤, MIP-5/HCC2, monocyte chemotactic protein (MCP)-1, MCP-2, MCP-3, MCP-4, RANTES (regulated on activation, normal T cell expressed and secreted), macrophage-derived chemokine (MDC), and the CXC chemokine stromal cell-derived factor (SDF)-1 [61][62][63].…”
Section: Chemokines Induce Directional Migration Of Dc/lcmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte chemoattractant protein (MCP)-1 is a small cytokine belonging to the CC chemokine family that recruits monocytes, memory T cells, and dendritic cells to sites of tissue injury, infection, and inflammation. 6,7 It is also induced by hypoxia and bleeding. [8][9][10][11] Clinical studies revealed that MCP-1 increased in the vitreous of patients with PDR and it was suspected of contributing to the progression of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes also secrete chemokines, particularly monocyte chemoattractant protein 1 (MCP-1). MCP-1 attracts leukocytes such as monocytes, T lymphocytes, and dendritic cells (Carr et al , 1994, Xu et al , 1996, which then secrete inflammatory cytokines such as interleukin-1 (IL-1), IL-6 and tumor necrosis factor-α. MCP-1 is also known to play a critical role in the development of cardiovascular disease and obesity-induced insulin resistance (Niu and Kolattukudy, 2009).…”
Section: Introductionmentioning
confidence: 99%